Exploitation, Justice, and Parity in International Clinical Research. (5th September 2013) - Panitch, Vida
Abstract: Consensus is lacking among research ethicists on the question of how broadly to understand the requirements of non‐exploitation in international clinical research. Two types of principles have been proposed, minimalist and non‐minimalist, grounded in two opposing conceptions of exploitation, transactional and systemic. Transactionalists have offered principles, which, it has been argued, are satisfied by minimal gains to vulnerable subjects measured against an unjust status quo. Systemicists have advanced principles with decidedly non‐minimal mandates but only by conflating the obligations of clinical research with those of First World citizenship. My aim here is to break this deadlock by offering grounds for a non‐minimal requirement of international research ethics grounded in a transactional conception of exploitation. I do this by arguing that a subject's gains must be measured not only within the transaction, relative to her own starting point and to the share of gains enjoyed by her co‐transactor, but also across transactions, so as to ensure parity of benefit to trial participants whenever, and wherever, parity of burden is assumed.